Rzecz o edukacyjnym kłamstwie - Śliwerski, Bogusław; Kobierski, Konrad (Annales. Etyka w Życiu Gospodarczym, 2008)
The subject of the analysis is within the category of an educational lie. According to MariaOssowska, this might be understood as either a justified or permitted misleading of someone,or the maintaining an illusion for either one’s own or another’s sake.Looking at different categories of these distortions of truth, we find that they are used not only fora child’s upbringing or the benefit of the topic, but for withholding or modifying the information aboutthe reality or educational concept. Cheating is an example of an educational lie and it combinessomeone’s opinion with truth, but would be falsely incompatible with factual knowledge and truthfulunderstanding. Pupils who cheat mislead the teacher and, in the instructor’s ignorance, are led to believethat those pupils have, in fact, knowledge reflected in the exam. Likely the teacher is being cheated aswell the student for different reasons. The educational lie has another dimension (when we take intoaccount the sham activity) the quasi teaching or the pseudo-education. This occurs wheneducators/teachers offer their pupils/clients something different from what should be. The pretencetakes place along with the authentic process of learning or completing educational tasks.